2020
DOI: 10.1007/jhep02(2020)196
|View full text |Cite
|
Sign up to set email alerts
|

Classification of dark pion multiplets as dark matter candidates and collider phenomenology

Abstract: New confining sectors can contain a set of pseudo-Goldstone mesons that exhibit a complicated structure in terms of stability and relative masses. Stable ones can act as dark matter candidates, while their interactions with the unstable ones determine their relic abundances. The overall structure, by specifying which channels are kinematically forbidden or not, affects the cosmology, constraints and collider phenomenology. In this paper, we present a classification of these pseudo-Goldstone meson structures. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 101 publications
0
9
0
Order By: Relevance
“…This spectrum was previously considered in a very different regime, with O(100) GeV dark meson masses[27].…”
mentioning
confidence: 99%
“…This spectrum was previously considered in a very different regime, with O(100) GeV dark meson masses[27].…”
mentioning
confidence: 99%
“…In the parameter region of interest, the ρ 0 d meson is predicted to decay promptly. 10 The most interesting constraints in the present context are therefore the ones searching for a narrow resonance in the e + e − , µ + µ − or π + π − final state. Specifically, we consider bounds from KLOE [39,40] and BaBar [37], which we obtain using Darkcast [63].…”
Section: Resonance Searchesmentioning
confidence: 98%
“…A promising strategy to explore this scenario is to try and produce dark sector states with sufficiently high energy that the fundamental constituents (i.e. dark quarks and gluons) are revealed and the details of hadronisation can be studied [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…in the context of twin Higgs models [11,12,13,14], composite and/or asymmetric dark matter scenarios [15,16,17,18,19,20,21,22,23,24,5,25,26,27], and string theory [28,29]. Some studies focusing on hidden valley phenomenology can be found in [30,31,32,33,34,35,36,10,37,38,39,40,41,42,6,43].…”
Section: Introductionmentioning
confidence: 99%